2017
DOI: 10.3389/fmicb.2017.00995
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Resources and Enological Significance: Opportunities and Benefits

Abstract: Among the innovative trends in the wine sector, the continuous exploration of enological properties associated with wine microbial resources represents a cornerstone driver of quality improvement. Since the advent of starter cultures technology, the attention has been focused on intraspecific biodiversity within the primary species responsible for alcoholic fermentation (Saccharomyces cerevisiae) and, subsequently, for the so-called ‘malolactic fermentation’ (Oenococcus oeni). However, in the last decade, a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 117 publications
(175 reference statements)
1
89
0
Order By: Relevance
“…non-Saccharomyces yeasts combined with S. cerevisiae in controlled mixed fermentations), mimicking the natural diversity associated with spontaneous fermentation, can be recommended to improve wine (Comitini et al, 2011;Ciani & Comitini, 2015;Campbell-Sills et al, 2016;Shekhawat et al, 2017). In this regard, the non-Saccharomyces species, Torulaspora delbrueckii, Metschnikowia pulcherrima, Candida zemplinina and Hanseniaspora uvarum, are cited and intensively investigated the most (Comitini et al, 2011;Medina et al, 2012;Masneuf-Pomarede et al, 2015;Petruzzi et al, 2017a), while strains belonging to the species Lachancea thermotolerans, Metschnikowia fructicola, Schizosaccharomyces pombe, T. delbrueckii, Kluyveromyces thermotolerans, Pichia kluyveri and M. pulcherrima are already commercialised Petruzzi et al, 2017a).…”
Section: Product Innovationmentioning
confidence: 99%
See 4 more Smart Citations
“…non-Saccharomyces yeasts combined with S. cerevisiae in controlled mixed fermentations), mimicking the natural diversity associated with spontaneous fermentation, can be recommended to improve wine (Comitini et al, 2011;Ciani & Comitini, 2015;Campbell-Sills et al, 2016;Shekhawat et al, 2017). In this regard, the non-Saccharomyces species, Torulaspora delbrueckii, Metschnikowia pulcherrima, Candida zemplinina and Hanseniaspora uvarum, are cited and intensively investigated the most (Comitini et al, 2011;Medina et al, 2012;Masneuf-Pomarede et al, 2015;Petruzzi et al, 2017a), while strains belonging to the species Lachancea thermotolerans, Metschnikowia fructicola, Schizosaccharomyces pombe, T. delbrueckii, Kluyveromyces thermotolerans, Pichia kluyveri and M. pulcherrima are already commercialised Petruzzi et al, 2017a).…”
Section: Product Innovationmentioning
confidence: 99%
“…Numerous studies on the influence of nonSaccharomyces yeast in winemaking have been undertaken on the oenological/technological relevance of these yeast species (Bely et al, 2008;Comitini et al, 2011;Sadoudi et al, 2012;Tristezza et al, 2016b;Petruzzi et al, 2017a). These studies demonstrated that non-Saccharomyces species could have both beneficial and negative influences on the wine fermentation characteristics, thus indicating the need to select strains with optimal oenological properties (Bely et al, 2008;Comitini et al, 2011;De Benedictis et al, 2011;Medina et al, 2012;Lu et al, 2015;Petruzzi et al, 2017a).…”
Section: Product Innovationmentioning
confidence: 99%
See 3 more Smart Citations